(untitled) (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted at Horticulture farm, Rajasthan College of Agriculture, Udaipur. The experiment comprised of sixteen treatment combinations consisting of four levels of zinc and boron (0, 0.2, 0.3 and 0.4%). The foliar spray of zinc and boron were done at pre-bloom and after fruit set stages. Foliar spray of zinc at 0.4% gave the maximum juice content (71.87%), ascorbic acid (8.04 mg/100 ml juice), TSS (21.72%), reducing sugar (4.54%), non-reducing sugar (1.76%), total sugar (16.30%) and gave lowest acidity (0.61%), while foliar spray of 0.2 per cent boron gave the maximum juice content (72.02%), Ascorbic acid (8.18 mg/100 ml juice), TSS (21.47%), reducing sugar (14.50%), non-reducing sugar (1.71%) and Total sugar (16.22%) and gave lowest acidity (0.60%).